Cross Roads, Wrong Tracks, or New Goals in Globalized Europe? - Zoltán Suti (DETUROPE)
A variety of motivations are needed to make people move house but, an even more profound determination is necessary to leave one’s home country. It is not simple to replant an old walnut tree but, sometimes, owing to the fertile soil and the new, favourable environment, replanting can bring richer harvest. True, in the 21st century the continuously changing and, at times, revolting Europe is opening up for new migrants. Yet, a modern-age adventure-seeking Ulysses has to face many challenges; the Great Unknown might hide good and bad as well, meaning, that the migrants’ knowledge and experience is often not enough: they often need much luck to succeed, too. In a globalized European Union migration processes are organic parts of life but, due to the intensifying nature of the trend a sensitive question needs to be asked from time to time. Is migration a chance or a danger? In consumer societies interpersonal relationships transform lifestyle, as well as people’s opinion concerning social mobility. Thus original social roots are being torn off, traditional relationships are fading and this is how a phenomenon called chameleon migration is established. As a result of the formerly mentioned processes temporary migration of work force is replaced by a new type of migration, aimed at uniting families. Thus the question inevitably arises: who stays at home and how do they cope?